INDIGENIZATION OF POVERTY CONCEPT: APPROACHMENT TO ISSUE OF URBAN POVERTY AND LOCAL GOVERNMENTS - Salih BATAL (Fırat University, 2019)
Poverty plays a part among the most important issues in today’s World. Even if it is different aspect for developed or developing countries, poverty issue plays a part among priority burning issues. Interrelatedness of concepts such as democracy, urban poverties, social state, social municipalism, poverty and urban poverty, after second part of the 20th century, as well as it cause new expansions and scholarly disputes, it has became an important constituent of our political world and social life. Poverty problem which fronts us with various versions in every moment of pür daily life is one of most confused punlic social problems that national and international organizations try to solve but they couldn't. Instutitions of political, economical and social is becoming significant in conjunction with changing of traditional centrist structure and understanting of social state. In conjunction with this improvement in local governments, folk provide more participants and thus management group exhibits more attitude to folk. In conjunction with indigenization and institutionalization of pluralistic democracy in developed countries, even material and nonmaterial developement moving that is one of the objective of social policy lead to gaining important of social municapility principle. In this study, birth of concept of urban poverty and its content will be came up by explaining of poverty concept and its varieties. Furthermore, struggle methods of local governments that is associated with urban poverty will be defined and some suggestions will be given for struggling of urban poverty.